Pedicle Screw Insertion with Intraoperative Triggered Electromyography Monitoring: A Review Article - Niljianskul, Nattawut (Thai Journal of Neurological Surgery, 2025)
The placement of pedicle screws (PS) has commonly used to treatment spinal pathologies including trauma, degenerative disease, scoliosis, and tumors. Accuracy for PS placement is very important and challenge due to malposition of PS and breached pedicle walls could lead to serious complication such as nerve root injury, spinal cord injury, vascular injury, dural laceration, visceral injury, pseudarthrosis, and instrument failure. Especially the nerve injury was the most common complication that confronted with spine surgeon. Despite technical advances over the last decades, PS placement is still associated with risk of complications. Intraoperative triggered electromyography (tEMG) is another intervention used to precisely place PS and avoiding nerve root injury. Intraoperative tEMG had the ability to detect pedicle breaches with fair sensitivity and high specificity. The probability of medial breach pedicle screw and post-operative neural integrity injury were correlated with low stimulation threshold.